2022
DOI: 10.3389/fendo.2022.873727
|View full text |Cite
|
Sign up to set email alerts
|

The Bradykinin System Contributes to the Regulation of Prostaglandin-Endoperoxide Synthase 2 Expression in Human Amnion Fibroblasts: Implications for Term and Preterm Birth

Abstract: BackgroundBradykinin (BK) and its biologically active metabolite des-Arg9 bradykinin (DABK) play a pivotal role in inflammation. Since chorioamnionitis is the leading cause of preterm birth and prostaglandin E2 (PGE2) derived from the amnion is key to labor initiation, we investigated if bradykinin peptides are part of the regulatory network of PGE2 synthesis in human amnion at parturition.MethodsHuman amnion tissue was obtained from term and preterm birth for the study of the changes of the bradykinin system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Here, in this study, we also demonstrated that MAPK and NF-κB pathways underpinned the IL-33 actions in ovarian CAFs. In mammals, MAPKs could be classified into three primary subfamilies, namely, JNK, ERK, and p38, which have been demonstrated to be associated with both infection and non-infection-induced inflammatory responses (Rodriguez-Barbero et al, 2006;Arthur and Ley, 2013;Ni et al, 2022). In this regard, we found that all three MAPKs were involved in the induction of IL-6, PGE2, and IL-1β expressions by IL-33 in ovarian CAFs, further indicating a crucial role of MAPKs in the inflammatory responses of the TM at OvC.…”
Section: Discussionmentioning
confidence: 99%
“…Here, in this study, we also demonstrated that MAPK and NF-κB pathways underpinned the IL-33 actions in ovarian CAFs. In mammals, MAPKs could be classified into three primary subfamilies, namely, JNK, ERK, and p38, which have been demonstrated to be associated with both infection and non-infection-induced inflammatory responses (Rodriguez-Barbero et al, 2006;Arthur and Ley, 2013;Ni et al, 2022). In this regard, we found that all three MAPKs were involved in the induction of IL-6, PGE2, and IL-1β expressions by IL-33 in ovarian CAFs, further indicating a crucial role of MAPKs in the inflammatory responses of the TM at OvC.…”
Section: Discussionmentioning
confidence: 99%
“…Des-Arg9-BK enhances angiogenesis under inflammatory conditions and the migration as well as invasion of cancer cells. 15,16 Moreover, MMD affects the blood-brain barrier (BBB), a complex network of specialized cells essential for maintaining a stable environment for the brain. BBB protects the brain from harmful substances in the blood.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…BK enhances the proliferative and migratory ability of ECs and stimulates new blood vessel formation in vivo. Des‐Arg9‐BK enhances angiogenesis under inflammatory conditions and the migration as well as invasion of cancer cells 15,16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amnion layer of the fetal membranes not only determines the tensile strength of the fetal membranes but also harbors a myriad of inflammatory signaling molecules (Menon et al 2020 ; Oyen et al 2006 ; Wang et al 2018 ). We and others have demonstrated that mesenchymal cells of the amnion produce a large amount of prostaglandins and pro-inflammatory cytokines (Keelan et al 1997 , 2003 ; Li et al 2017 ; Ni et al 2022 ; Okazaki et al 1981 ; Zhang et al 2017 ). Therefore, understanding the expression and regulation of pro-inflammatory signaling molecules in amnion mesenchymal cells may help further understand the unresolved mechanisms of human parturition.…”
Section: Introductionmentioning
confidence: 96%